2013
DOI: 10.1055/s-0033-1358603
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody-Associated Movement Disorders

Abstract: Autoantibodies to the extracellular domain of neuronal proteins cause different neurological conditions with movement disorders as a prominent feature. We reviewed the literature of autoantibody-mediated and autoantibody-associated diseases focusing on anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, autoimmune basal ganglia encephalitis, Sydenham chorea, and the rare syndrome of progressive encephalomyelitis with rigidity and myoclonus. NMDAR encephalitis is a diffuse encephalitis with psychiatric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 83 publications
(113 reference statements)
1
25
0
Order By: Relevance
“…Flow Cytometry Live Cell-Based Assay for Detection of Antibodies to Cell Surface D2R and NR1 in Serum Flow cytometry live cell-based assay was used to detect immunoglobulin binding from serum to transfected HEK293 cells, as previously described (26)(27)(28)(29). After transfection, cells were cultured for 2 days.…”
Section: Immune-mediated Mechanisms In Childhood Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Flow Cytometry Live Cell-Based Assay for Detection of Antibodies to Cell Surface D2R and NR1 in Serum Flow cytometry live cell-based assay was used to detect immunoglobulin binding from serum to transfected HEK293 cells, as previously described (26)(27)(28)(29). After transfection, cells were cultured for 2 days.…”
Section: Immune-mediated Mechanisms In Childhood Psychosismentioning
confidence: 99%
“…Cox et al (45) recently reported that a monoclonal IgM antibody derived from a patient with Sydenham chorea bound to human D2R, inducing signaling comparable with that seen after dopamine binding, as measured by levels of cyclic adenosine monophosphate. Furthermore, in the context of autoimmune encephalitis, serum surface D2R and NR1 antibody titers seem to correlate with improvement in clinical status and immunotherapy has proved effective (21,29,46). Existing evidence already suggests that NR1 IgG antibodies are pathogenic in NMDAR encephalitis (15).…”
Section: Immune-mediated Mechanisms In Childhood Psychosismentioning
confidence: 99%
“…The associated autoantibodies can be directed against intracellular or extracellular autoantigens [13], and the clinical phenotype of patients is diverse, encompassing movement disorders and neuropsychiatric disorders [4, 5]. Antibodies targeting intracellular antigens are not considered pathogenic but are sometimes believed to be biomarkers of an underlying tumor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hypotonia is seen in most patients and, when severe, 2% of patients develop a flaccid quadriparesis often labeled as "chorea paralytica." 21 SC is an autoimmune process, a definitive autoantibody has not been found. Sixty percent to 80% of patients have cardiac involvement 22 and half of the patients still have chorea 2 years after onset of symptoms.…”
Section: Sydenham Choreamentioning
confidence: 99%
“…Valproic acid or carbamazepine, rather than neuroleptic therapy, are preferred for symptomatic treatment. 21 Antibiotic prophylaxis following the acute rheumatic fever guidelines until the age of 21 is recommended to avoid rheumatic heart disease. 21 …”
Section: Sydenham Choreamentioning
confidence: 99%